DESIGN OPTIMIZATION OF BATTERY CAR PROTECTION SYSTEM USING AUXETIC STRUCTURE SUBJECTED TO SIDE POLE IMPACT - Satria Jatinendra, Yohanes
The use of electric cars has increased rapidly in the world due to increasing awareness among car manufacturers and the public about the threat of global warming caused by emissions by conventional cars. The majority of electric cars on the roads today utilize batteries as their primary method of electrical energy storage. Despite playing the most important role in electric cars, batteries also pose the biggest threat to electric cars. With a high energy density, batteries are prone to catch fire or even explode if exposed to impact loads. Therefore, a car battery protector is needed so that when something unwanted happens, such as the car hit a pole from the side, the battery does not fail and not get burnt. Auxetic structures possess a distinctive feature - a negative Poisson's ratio (NPR). This property grants them numerous advantages over conventional structures, notably a remarkable energy absorption capacity, especially under localized loading such as side pole impact. Therefore, auxetic structures are poised to be engineered as efficient safeguards for battery cars against side pole impact loads. Through this research, there are some objectives carried out within this research, first is to model and calculate crashworthiness performance of 2D auxetic baseline. Additionally, it aims to conduct a comparative analysis of specific energy absorbed (SEA), maximum displacement (Smax), and maximum force (Fmax) between auxetic structures and positive Poisson’s ratio structures (PPR). Lastly, the goal is to obtain specifications for the dimensions and shape of a battery car protection structure that has been optimized using an auxetic structure, considering SEA and Smax. The methodology conducted within this research are as follows, the initial step involves conducting a comprehensive literature study, followed by modeling and validation of a preexisting structure developed in previous research by using finite element analysis software. Subsequently, the actual design is modelled and sampled, and then the optimization process utilizes machine learning techniques, where 2nd degree polynomial regression and NSGA II methods are employed to effectively optimize the auxetic structure. The optimization aims to achieve two objectives: specific energy absorption (SEA) and maximum displacement (Smax). In conclusion, SEA with value of 2180.41 J/kg and Smax with value of 80.79 mm were obtained for structure composed of double arrowhead honeycomb cells with: ????1 = 60.37????, ????2 = 22.67????, L = 6.26 mm, and t = 1.01 mm.